Strategi PAK Ditinjau Dari Sudut Pandang Sosiologi Pendidikan - Sirait, Rajiman Andrianus (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Indonesian students' character is greatly shaped by Christian Religious Education, but in an age of globalisation and religious diversity, PAK practices must be updated and adjusted to the changing social environment. This study applies insights from educational sociology to analyse successful PAK tactics. The ideas of Christian education and sociological theories of education are used to emphasise difficulties and barriers in putting the PAK strategy into practice through qualitative library study methodologies. The results highlight the significance of comprehending ideological disputes in societies, changing curricula to reflect cultural and technological advances, and focusing on the symbolic interaction between teachers and students. The findings lay the groundwork for the creation of more pertinent and potent religious instruction.